2021
DOI: 10.1016/j.ajpc.2021.100280
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of blood pressure skills and belief in clinical readings

Abstract: Background Accurate blood pressure (BP) measurement is essential for the diagnosis and management of hypertension. In clinical practice, BP is estimated using noninvasive methods with significant variability of application of guidelines in clinical practice, impacting the accuracy and certainty of BP measurements. Objective We sought to assess how BP is measured in clinical practice. Methods A survey was administered through professional soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…This is consistent with another study conducted among healthcare professions to determine the knowledge of blood pressure measurement skills, where one in ve persons measured blood pressure correctly. 22 It is also consistent with studies conducted among nurses which revealed irregularities in the blood pressure assessment technique at baseline evaluation which is due to the fact that there was inadequate emphasis on correct technique and lack of periodical retraining. 23 Results from our study contradict what was reported in a community based hypertension screening study performed by health extension workers and trained health professionals where high blood pressure was detected in a dependable way using an aneroid sphygmomanometer.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with another study conducted among healthcare professions to determine the knowledge of blood pressure measurement skills, where one in ve persons measured blood pressure correctly. 22 It is also consistent with studies conducted among nurses which revealed irregularities in the blood pressure assessment technique at baseline evaluation which is due to the fact that there was inadequate emphasis on correct technique and lack of periodical retraining. 23 Results from our study contradict what was reported in a community based hypertension screening study performed by health extension workers and trained health professionals where high blood pressure was detected in a dependable way using an aneroid sphygmomanometer.…”
Section: Discussionsupporting
confidence: 87%
“…As a result, clinical practice is unclear and lacking in standards. The majority of guidelines advise ambulatory and athome blood pressure monitoring to confirm diagnoses outside of the clinic [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, these numbers differ significantly between countries [2]. Less than 1 in 5 are estimated to have their blood pressure under effective control, which contributes to more than 10 million deaths annually [3,4]. Hypertension is a significant but avoidable risk factor for heart failure, chronic renal disease, haemorrhagic and ischemic stroke and coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate BPM is important in the diagnosing and managing HTN. The reliability of BPM needs education, the recognition of recommendation implementation barriers, and engagement of the entire team [ 28 ]. Releasing staff from practice to present classroom teaching or arranging their release and fitting training according to their shifts is difficult.…”
Section: Discussionmentioning
confidence: 99%